Performance optimization of domestic refrigerator using experimental method - Law, Chee Hong (2009)
This thesis deals with optimization performance testing for a domestic refrigerator using experimental method. As the refrigeration system has become one of the basic needs to us, the actual working principle is essential to be known by us so that we can always optimize the system performance and minimize the resources used. The objectives of this thesis is to improve a previous developed mini domestic refrigerator test rig by modifying the configuration of its tubing system, investigate the effect of refrigerant quantity on refrigeration system, and optimization performance of the mini domestic refrigerator test rig. The thesis describes the step by step fabrication of the tubing system of the mentioned test rig to achieve a simplest tubing system configuration for this refrigerator test rig. Vapor compression refrigeration system was studied as it is the most widely used refrigeration system especially in small scale of refrigeration application such as in domestic application. The design of the simpler tubing system will be depend on the location of other components in refrigeration system are located. The previous developed lengthy tubing system was greatly reduced in length by removing the thermocouple wires from the tubing system and moved it to the outer surface of the tubing. The improved refrigerator test rig was run and observed by using different quantity of refrigerant. The pressures and temperatures at the points of interest were observed and collected for all quantity of refrigerant. Finally, obtained the enthalpies for each of the points of interest and the optimum refrigeration coefficient of performance, , by using equations given. From the results, it is observed that the quantity of refrigerant does give significant effect on the performance of the refrigeration system. The obtained results indicate that there is a optimum point of refrigerant quantity for a particular refrigeration system depends on the capacity of the components in the system. The results concluded that the optimum performance achieved at the 35 psi initial charged refrigerant quantity which is at the lower refrigerant quantity out of the testing range of 35 to 45 psi initial refrigerant charged quantity. The results can contribute to understanding of the actual working principle of refrigeration system.